2008
DOI: 10.1103/physreva.78.042114
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence and disentanglement for two qubits in a common squeezed reservoir

Abstract: We study the relation between the sudden death and revival of the entanglement of two qubits in a common squeezed reservoir, and the normal decoherence, by getting closer to the Decoherence Free Subspace and calculating the effect on the death and revival times.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…Let us recapitulate the observation made in Ref. [29] about the Markovian dynamics of entanglement for the state |Ψ 1 in the parameter interval 0 ≤ ǫ < 0.5 [see also the curve in dashed line in Fig. 1(a)], where it was shown that the initial entanglement decays to zero in a finite time t d .…”
Section: Numerical Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Let us recapitulate the observation made in Ref. [29] about the Markovian dynamics of entanglement for the state |Ψ 1 in the parameter interval 0 ≤ ǫ < 0.5 [see also the curve in dashed line in Fig. 1(a)], where it was shown that the initial entanglement decays to zero in a finite time t d .…”
Section: Numerical Resultsmentioning
confidence: 57%
“…Similar multiple death and revival cycle is observed for the state with ǫ = 0.5 in the non-Markovian case showing a clear departure from the Markovian dynamics. When 0.5 ≤ ǫ < 1, that is when we get closer to the Markovian DFS, it was shown [29] that the whole phenomenon of sudden death and revival disappears for the initial state |Ψ 1 . Contrary to that, we see [for the initial state |Ψ 1 with ǫ = 0.9 in Fig.1(c)] clear sudden death and revival for this range of ǫ as well in the non-Markovian case.…”
Section: Numerical Resultsmentioning
confidence: 89%
See 3 more Smart Citations